2021
DOI: 10.1053/j.jvca.2021.06.017
|View full text |Cite
|
Sign up to set email alerts
|

So You Want to Write a Narrative Review Article?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…There are many different literature search engines (e.g. PubMed, EMBASE, Google Scholar); however, these are only as good as the user – the skill and enthusiasm of the author will make or break this process [16].…”
Section: Reporting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different literature search engines (e.g. PubMed, EMBASE, Google Scholar); however, these are only as good as the user – the skill and enthusiasm of the author will make or break this process [16].…”
Section: Reporting Methodsmentioning
confidence: 99%
“…There are many different literature searchengines (e.g. PubMed, EMBASE, Google Scholar); however, these are only as good as the userthe skill and enthusiasm of the author will make or break this process[16].Once you have completed the initial search, organise the articles (by sub-topic and then chronologically is a good way to start) and start to read. As you read, make notes, and get the articles used as references.…”
mentioning
confidence: 99%
“…A revisão narrativa de literatura busca trazer tópicos consolidados e novas perspectivas sobre um tema em questão, sendo de fundamental importância na área da saúde, e principalmente no campo da medicina (Chaney, 2021). As revisões narrativas, como esta, visam apresentar uma compreensão abrangente sobre os dados disponíveis na literatura acerca de um tema ou tópico específico, sendo direcionada por protocolos específicos, além disso, busca identificar omissões ou lacunas e obter novos insights a partir da identificação de conexões não óbvias anteriormente desconhecidas, desenvolvendo assim novas concepções (Butler et al, 2016;Chaney, 2021).…”
Section: Estratégia De Pesquisaunclassified
“…A revisão narrativa de literatura busca trazer tópicos consolidados e novas perspectivas sobre um tema em questão, sendo de fundamental importância na área da saúde, e principalmente no campo da medicina (Chaney, 2021). As revisões narrativas, como esta, visam apresentar uma compreensão abrangente sobre os dados disponíveis na literatura acerca de um tema ou tópico específico, sendo direcionada por protocolos específicos, além disso, busca identificar omissões ou lacunas e obter novos insights a partir da identificação de conexões não óbvias anteriormente desconhecidas, desenvolvendo assim novas concepções (Butler et al, 2016;Chaney, 2021). Como protocolo para o delineamento da revisão, além da escolha do tema, são selecionados bancos de dados para a pesquisa bibliográfica, sendo determinados critérios de inclusão e exclusão para os trabalhos alinhados com o tema proposto, assim como delimitadas palavras-chave para o direcionamento da seleção das publicações de interesse.…”
Section: Estratégia De Pesquisaunclassified
“…As such, it would be worthwhile for academic leaders to introduce other methods of publication such as case reports, narrative reviews, and perspective-type articles that are offered in many medical journals. Although there are publications instructing authors in how to write a case report 1,2 and narrative review, 3,4 we found none cited in PubMed detailing the rationale and steps for writing a perspective article. For authors inexperienced in writing, not considering perspective-type articles is a wasted opportunity for potential publication.…”
mentioning
confidence: 97%